Algeria’s fiscal policy and its implications for economic ‎performance: An analytical study for the period (2001-2014)‎ - Tebaibia, Salima; Anani, Sassia (Dirassat Journal Economic Issue, 2017)
This study is an attempt to assess the effectiveness and success of the monetary policy pursued by Algeria during the period (2001-2014), and by measuring their impact on economic stability indicators. It has been reached by the results of the study to the ineffectiveness of expansionary fiscal policy followed during the study period, given that one of the basic objectives is to achieve growth outside the hydrocarbon is still a long investigation, which has been detected it through a drop in oil prices, with the mid-year 2014, which led the government to change its policies through the adoption of austerity measures to cope with the crisis, and to emphasize the importance of strengthening the diversification of economic activities and orientation towards building a strong industrial base.